Experimental evaluation of cold storage performance coupled with an insert incorporated air heater and Humidification Dehumidification (HDH) system - K. Srithar; M. Rishidev; M. Kaveri; R. Saravanan (International Journal of Thermofluids, 2025)
An insert incorporated air heater in Humidification Dehumidification (HDH) desalination system combined to a Vapor Compression Refrigeration (VCR) system is a unique combination to ramp up the performance of the cold storage along with fresh water production. A research lacuna exists in the exploration of the different air heater inserts and its influence on the cold storage performance. The aim of this work is to explore different inserts (Continuous Helical Insert with Square Holes (CHISH), Discontinues Helical Insert with Square Holes (DHISH), Discontinuous Helical Insert with V Winglets (DHIVW) and Y shaped Inserts (YI)) and to evaluate the functioning of the cold storage modified with a HDH system with an air heater. Flow conditions of air was varied from 0.027 to 0.087 kg/s. At ideal flow conditions and with 0.2 kW refrigeration load the revamped system comprising unique Y shaped Inserts (YI) in air heater which exhibited less friction loss due to its geometric design and perforations having a Thermal Enhancement Factor (TEF) of 3.09 the cold storage has showcased exemplary performance attaining a Coefficient of Performance (COP) of 3.14, with energy consumption of 0.6 kWh producing – 65 ml of water during the operational time of 39 min. Triple achievement that is COP enhancement of 18.93 % and energy consumption reduction of 25 % is along with the production of indispensable fresh water as an additional output is obtained in this study.